PENERAPAN TOTAL QUALITY MANAGEMENT DALAM MENINGKATKAN KUALITAS PRODUK TEH HITAM (Studi Kasus Pada PT. Xyz, Kabupaten Bandung) - Yamandita Adzkia; Eddy Renaldi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Product quality is an important aspect for consumers that can affect the continuity of the company. PT. XYZ, which is a black tea commodity company with orthodox processing, has strived to always produce quality products. However, in the process there are still product defects. Through the application of total quality management, this study aims to determine the application of product quality management, to determine the factors of product defects, and to determine the sequence of improvements that can be made. This study uses a mix method design with case study research techniques. The first and second objectives were analyzed descriptively using the Statistical Quality Control tool, while the third objective was analyzed using the Analytical Hierarchy Process method. The results showed that quality planning experienced obstacles in the form of budget delays, scarcity of raw materials, and broken machines. Quality control is beyond the control limits due to quality defects of 2.46%. Product quality assurance is carried out through organoleptic testing. Quality improvement has not been implemented comprehensively in both the plantation and processing areas. Improvements that need to be made successively are density due to non-standard inlet temperatures, smallish due to incorrect blend composition settings , powdery due to a strong and repeated pressing process, and smokey due to lack of checking engine condition.